Mitigasi Gempa dan Tsunami di Kota Padang - Novia Winda Sari; Susi Sulandari; Dyah Lituhayu (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2014)
Recognize that Padang City has a high potency of earthquake and tsunami, Badan Penanggulangan Bencana Daerah dan Pemadam Kebakaran (BPBD-PK) of Padang City is formed as the Coordinator and Implementor of Disaster Management at the local level. The mitigation activities used to reduce the hight risk of negative effect of the earthquake andtsunami such as formulate regulations as a reference of mitigation, hazard maps, socialization and simulation, procure The Early Warning System, Determination of earthquake-safeconstruction, and manufacturing lines and evacuation (shelter). Conservation of coastal forests do not become the main focus of the Government of Padang City.Mitigation earthquake and tsunami based on principle of coordination in order to deploy and mobilize all the resources that needed to actualize the prevention and preparednesssuccesfully in Padang City. There are some constraints that used to faced are limited funds, the lack of apparatus ability, and the high level of the turn-over of employees. Based on the results of the research, Researcher recommend that the strengthening of cooperation with other parties in order to overcome obstacles in implementing the mitigation of earthquake and tsunami.